Synthesis of MgB2 from Mgb4 through combinatorial solid state reaction routes. - Tan, K. L.; Tan, K. Y.; Lim, Kean Pah; Abdul Halim, Shaari; Chen, Soo Kien (Malaysian Solid State Science and Technology Society (MASS), 2011)

(untitled)
MgB4 was first prepared from the elemental magnesium and boron powders, followed by acid-washed in order to remove the primary impurity of MgO. In the second step, appropriate amount of Mg was added into the MgB4 powders and sintered in the temperature range of 650°C to 950°C for 8 hours. XRD spectra showed that MgB2 appeared as the main phase. The relative intensity fraction for MgB2 was found to decrease while this value was increased for MgB4 and MgO upon increasing the sintering temperature. Scanning electron microscopy showed a denser microstructure compared to samples prepared by direct in-situ reaction of (Mg + 2B). The density was found to decrease with increasing sintering temperature possibly due to the loss of Mg.